2023
DOI: 10.5194/acp-23-2199-2023
|View full text |Cite
|
Sign up to set email alerts
|

On the global relationship between polarimetric radio occultation differential phase shift and ice water content

Abstract: Abstract. The Radio Occultations and Heavy Precipitation (ROHP) experiment aboard the Spanish PAZ satellite was deployed in 2018 with the objective of demonstrating the ability of the polarimetric radio occultation measurement (PRO) concept in detecting rain (liquid-phase precipitation). Analysis of these data has also demonstrated the ability of PRO to detect horizontally oriented frozen-phase precipitation. To verify these observations, a global climatological comparison is performed using the CloudSat (94 G… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…There are two main reasons behind this shape: (1) The first one is that the PRO observable ∆Φ is sensitive to frozen hydrometeors, as long as they are horizontally oriented (e.g. Padullés et al, 2022Padullés et al, , 2023, and these are placed above the freezing level;…”
Section: Polarimetric Products: Differential Phase Shiftmentioning
confidence: 99%
See 2 more Smart Citations
“…There are two main reasons behind this shape: (1) The first one is that the PRO observable ∆Φ is sensitive to frozen hydrometeors, as long as they are horizontally oriented (e.g. Padullés et al, 2022Padullés et al, , 2023, and these are placed above the freezing level;…”
Section: Polarimetric Products: Differential Phase Shiftmentioning
confidence: 99%
“…The fact that ∆Φ is sensitive to frozen hydrometeors, and that these are horizontally oriented, globally, and for different types of clouds (e.g. Gong and Wu, 2017;Zeng et al, 2019;Padullés et al, 2023) implies that the ∆Φ signature should have a relationship with the tops of the clouds. Being a measurement at L-band, it is expected that sensitivity to clouds starts below the cloud top height (as inferred from the infrared, for example).…”
Section: Polarimetric Products: Top Of the Signalmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has also been shown that the PRO observable ∆Φ increases with higher precipitation rain rates, indicating also sensitivity to precipitation intensity. Moreover, subsequent studies have shown that PRO is not only sensitive to precipitation, but also to horizontally oriented frozen hydrometeors found in various vertical layers of convective clouds [8,9]. This sensitivity is particularly pronounced for snow, where aggregated ice crystals produce relatively large hydrometeor particles.…”
Section: Introductionmentioning
confidence: 98%